Allergenicity of pasteurized whole raw Hen's egg compared with fresh whole raw Hen's egg. Issue 3 (May 2015) - Netting, Merryn; Donato, Adaweyah; Makrides, Maria; Gold, Michael; Quinn, Patrick; Penttila, Irmeli
Abstract: Background: Oral food challenges for diagnosis and management of egg allergy using fresh egg are common; however, to limit the risk of foodborne infection, many allergy units use pasteurized raw egg. Pasteurization and drying processes have the potential to affect the structure of egg proteins in egg powder and thus the allergenicity when compared to fresh egg. Our aim was to compare the binding of serum IgE from egg‐allergic children to in vitro digested and undigested pasteurized whole raw egg powder with unpasteurized fresh whole raw egg. Methods: Egg proteins from in vitro digested or undigested pasteurized whole raw egg powder, fresh whole egg, egg white and egg yolk were separated by SDS‐PAGE, transferred onto nitrocellulose membrane and incubated overnight with pooled sera from egg‐allergic children. Results: In both the raw egg samples and the pasteurized whole egg powder, protein bands corresponding to known molecular weights of the major egg allergens were present. Pasteurized whole raw egg powder was bound by serum IgE in a similar manner to unpasteurized whole raw egg and was unaffected by in vitro digestion. Serum IgE also bound egg yolk, indicating sensitization to both egg yolk and egg white proteins. Conclusions: The main egg allergens are present in pasteurized whole raw egg powder, and serum IgE of egg‐allergic children binds to them in a similar pattern to those in fresh whole raw egg. Pasteurized whole raw egg powder is a suitable substitute for raw egg in clinical practice for oral food challenges.